Competing after Radical Technological Change: The Significance of Product Line Management Strategy - JONES, Neil (Institutional Knowledge at Singapore Management University, 2003)
Research on firm performance after the introduction of a radical technological change has primarily concerned itself with difference between incumbents and entrants. This paper explores other factors that may influence firm performance over the longer term after a radical change--specifically, those related to product line management strategy. Following a radical change, a period of incremental technological change typically creates the opportunity for rapid development of new products. In such settings, strategies to manage multiple products, including families of related products that can be derived from a common platform, may be expected to impact competitive performance, especially over the longer term. The data for the study are from the telecommunications switching sector, specifically the private branch exchange (PBX) industry. Fifty-six firms and over 240 new products were analyzed over 22 years. This study shows that incumbent--entrant-based explanation of firm performance are incomplete. In particular, the results demonstrate that product line strategy explains significant additional variation in firm performance. The paper tests hypotheses linking both overall product line strategy and product platform strategy to firm performance. It also shows that decomposing overall strategy into product platform strategy - rates of platform and derivative introduction, and platform longevity - can further increase explanatory power. In total, the results indicate that strategic prescriptions in the literature that emphasize development speed alone are oversimplified. They also suggest that differences in how relationships among products derived from a common platform are managed can attribute to competitive advantage and demand complex trade-offs.